Analisis Kepuasan Customer terhadap Produk Cokelat Almond pada Kewirausahaan - Alfi Falah Aghnia; Rizka Inayatul Ummah; Tegar Pratama; Amin Sadiqin (PUTRA JAWA PUBLISHER, 2023)
Chocolate is a product made from chocolate ingredients that are very easy to find. Therefore, providing a large amount of chocolate bars can be very helpful. In this way, there is no need to worry about running out of the main base material, which will later become the most important base ingredient of chocolate. There are still many different variations and toppings such as almonds, walnuts, cashews, etc. Indonesia's cocoa farming industry is currently developing. Various countries, including Indonesia, produce nuts, with almonds serving as the main raw material. On this occasion, we intend to create an entrepreneurial spirit with a product called “almond chocolate” that produces various types of chocolate products both on an industrial scale and small businesses. One of the producers of processed chocolate products is Kampung Coklat. This study aims to determine consumer satisfaction with processed almond chocolate products. This study uses descriptive analysis techniques with business feasibility studies and direct observation of products thrown as entrepreneurs to determine the characteristics of processed almond chocolate products that need to be improved. This is intended so that the attributes included in the level of consumer satisfaction with processed almond chocolate products can be maintained. Producers need to improve properties whose performance has not reached consumer satisfaction in order to increase consumer satisfaction and present a positive image for students of ongoing business activities.